Szent Jeromos és Szent Ágoston vitája a fordításról - Takács, László (Antikvitás & Reneszánsz, 2019)
During the revision of the earlier translation of the Book of Jonah St Jerome changed the name of the fast-growing plant referred to in the story. In his version it is ivy that sprang up and perished in a day instead of gourd. St Augustine (Bishop of Hippo) wrote a letter to St Jerome expressing his discontent about the ivy-version. According to his argumentation disturbance broke out among the Greek and Roman Christian communities in the city of Oia as a result of the differences of the translations: the Greeks used the version of Septuaginta (gourd), while the Romans used the new St Jerome-translation (ivy). In his response St Jerome rejects St Augustine’s criticism and explains what his reason was for his departure from the customary text. The paper tries to illustrate that St Jerome, who knew the plant properly, favoured the Latin-speaking communities of Europe, when he inserted the word ivy into the text.